Carbon-black combined with TiO2 and KuQ as sustainable photosystem for a reliable self-powered photoelectrochemical biosensor. (10th September 2022) - Mazzaracchio, Vincenzo; Marrone, Roberta; Forchetta, Mattia; Sabuzi, Federica; Galloni, Pierluca; Wang, Mingqing; Nazligul, Ahmet; Choy, Kwang-Leong; Arduini, Fabiana; Moscone, Danila
Abstract: Since our first work published in Electrochemistry Communication in 2010 (12, 346–350), many carbon black-(CB) based electrochemical printed (bio)sensors have been reported in the literature, addressing voltammetric and potentiometric measurements. Herein, we report the first photoelectrochemical biosensor based on a printed electrode modified with CB. In detail, the photoelectrochemical sensor has been designed by using, in addition to CB, and TiO2, KuQ dye because the use of only TiO2 and CB still requires UV irradiation, while KuQ is characterized by a broad and intense absorption spectrum in the visible region allowing for an easy set-up with a cost-effective portable laser. Once optimized the fabrication and working conditions, namely the solvent for the TiO2 dispersion (i.e. water/dimethylformamide (1:1 v/v)), the amount of TiO2 /KuQ to cast onto the working electrode surface (i.e. 4 μg), the applied potential (i.e. +0.4 V), and the working solution (i.e. Tris buffer at pH 8.8), the sensor was challenged for NADH measurement obtaining a linear range up to 8 mM and a detection limit, calculated as 3 σb /slope, equal to 20 µM. The subsequent immobilization of Alcohol Dehydrogenase demonstrated the capability of this biosensor to detect ethanol up to 1 M, with the detection limit equal to 0.062 mM, indicating that the CB-TiO2 /KuQ modification can regenerate the coenzyme even in the immobilized form, with improved analytical performances in terms of enhancement of the linearity. Finally, ethanol was detected in a real sample, i.e. white wine, with a good recovery value of 91.60 ± 0.01%, demonstrating the applicability of the developed miniaturized biosensor in white wine samples.